Determinants of Profitability in Indian Banks in the Changing Scenario - Mohanty, Biraj Kumar; Krishnankutty, Raveesh (International Journal of Economics and Financial Issues, 2018)
Banking Sector in India plays a crucial role in the development of the country. Being a major constituent of the economy, banks have their own promises and challenges. While banks have the onus of providing funds to the growing economy, they face a daunting task of maintaining profitability in a competitive environment. This study aims at identifying the performance variables responsible in driving the Return on Asset (ROA) of the banks. We have analyzed bank specific, industry specific and economy specific elements guiding the profitability of 46 Indian banks over a period of 17 Years (1999-2015) through panel Generalized Method of movements (GMM) estimation. It was found out that Return on Asset (ROA) has a significant positive association with last year ROA, solvency ratio, capital adequacy ratio whereas two and three year lag ROA, size, GDP growth, Loan to Deposit Ratio, expense ratio and productivity have significant negative effect. Keywords: Profitability of Banks, Panel GMM estimation, JEL Classifications: E50, C23, C33